2022
DOI: 10.1142/s0218216522500675
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular knot diagrams classification with deep learning

Abstract: In this paper, we discuss applications of neural networks to recognizing knots and, in particular, to the unknotting problem. One of the motivations for this study is to understand how neural networks work on the example of a problem for which rigorous mathematical algorithms for its solution are known. We represent knots by rectangular Dynnikov diagrams and apply neural networks to distinguish a given diagram’s class from a finite family of topological types. The data presented to the program is generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Very recently the use of supervised ML approaches based on neural networks (NNs) has been recognized as a valuable tool in providing new insights into the mathematical problem of knot identification. In ref , it was shown that a specific NN architecture, the long–short-term memory (LSTM) NN, can learn some global properties of the system that help with identifying the knotted state, once trained on sequences of bond directions along a semiflexible polymer ring of length N = 100.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently the use of supervised ML approaches based on neural networks (NNs) has been recognized as a valuable tool in providing new insights into the mathematical problem of knot identification. In ref , it was shown that a specific NN architecture, the long–short-term memory (LSTM) NN, can learn some global properties of the system that help with identifying the knotted state, once trained on sequences of bond directions along a semiflexible polymer ring of length N = 100.…”
Section: Introductionmentioning
confidence: 99%
“…We find that GEN+GAT model significantly outperforms the other models GCN+GAT and GCN+GCN. The model GCN+GAT seems to outperform GCN+GCN by few percent, but the performance difference is negligible 7 .…”
Section: Resultsmentioning
confidence: 90%
“…It is natural to apply GDL techniques also to mathematical problems in topology. In general, ML has been already used in various problems in low-dimensional topology, knot theory in particular, [3][4][5][6][7][8][9][10][11][12], as well as various physics-related problems in geometry (for a recent survey see [13]). However, the used neural network models were mostly not specific to GDL.…”
Section: Introductionmentioning
confidence: 99%